2016
DOI: 10.3390/su8060565
|View full text |Cite
|
Sign up to set email alerts
|

Soil Conservation Issues in India

Abstract: Despite years of study and substantial investment in remediation and prevention, soil erosion continues to be a major environmental problem with regard to land use in India and elsewhere around the world. Furthermore, changing climate and/or weather patterns are exacerbating the problem. Our objective was to review past and current soil conservation programmes in India to better understand how production-, environmental-, social-, economic-and policy-related issues have affected soil and water conservation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
(36 reference statements)
1
18
0
1
Order By: Relevance
“…On the contrary, Wang et al [92] found improvement in the state of erosion risk in the Danjiangkou reservoir area, China, where the eroded areas have declined from 32.1% in 2004 to 25.43% in the 2010 study period. Moreover, Jiang et al [16] reported that the eroded area has Therefore, since there is geospatial variation in soil erosion risk distribution across the watershed area, identification of priority area is the key factor for planning and implementing appropriate SWC [10][11][12][13][14][15][16][17][18][19]51,90,142]. Accordingly, we prioritized areas with a higher and increasing soil loss rate as SWC priority areas (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Wang et al [92] found improvement in the state of erosion risk in the Danjiangkou reservoir area, China, where the eroded areas have declined from 32.1% in 2004 to 25.43% in the 2010 study period. Moreover, Jiang et al [16] reported that the eroded area has Therefore, since there is geospatial variation in soil erosion risk distribution across the watershed area, identification of priority area is the key factor for planning and implementing appropriate SWC [10][11][12][13][14][15][16][17][18][19]51,90,142]. Accordingly, we prioritized areas with a higher and increasing soil loss rate as SWC priority areas (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that conservation agriculture is practiced on less than 1% of the total cropland area in India (e.g., Bhattacharyya et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…To implement this option, policy measures are required to address cost‐related factors and provide incentives for residue recycling, given that currently residue burning is increasing attributable to the use of combined harvesters (grain and straw simultaneously), limited labor force, and lacking economic incentives (Bhattacharyya et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations